2013
DOI: 10.1111/cod.12035
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization patterns in Compositae‐allergic patients with current or past atopic dermatitis

Abstract: Persons with current or past atopic dermatitis may become sensitized to Compositae at any age, both occupationally and non-occupationally. They should be screened for Compositae allergy on equal terms with non-atopics, except that dandelion extract should always be tested in children. Co-sensitization to cobalt was frequent, but probably not related to the plant allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
(93 reference statements)
0
20
0
Order By: Relevance
“…Weak allergens, such as lanolin alcohol, can result in sensitisation following exposure over many years . Increasingly, SL mix sensitivity has been associated with AD, and may be mediated via inhalation of airborne pollen or usage of topical products with compositae allergens …”
Section: Discussionmentioning
confidence: 65%
“…Weak allergens, such as lanolin alcohol, can result in sensitisation following exposure over many years . Increasingly, SL mix sensitivity has been associated with AD, and may be mediated via inhalation of airborne pollen or usage of topical products with compositae allergens …”
Section: Discussionmentioning
confidence: 65%
“…Previous studies and case reports have suggested an increased risk of sensitization to plant allergens in patients with AD, but the causality of this relationship is unclear. Although few of the reviewed studies provide information on contact allergy to sesquiterpene lactone mix and compositae mix, positive reactions were significantly associated with AD.…”
Section: Discussionmentioning
confidence: 97%
“…A periumbilical, neck and wrist, or earlobe dermatitis might indicate exposure to nickel in the claps of jeans, necklace, bracelets, or earrings [28]. It is important to always ask about use of natural remedies in parallel to prescribed treatments, which may sustain the symptoms of ACD in children [29], with particular attention on the use of essential oil and Compositae dermatitis, which may appear as hand eczema in young children [30].…”
Section: Clinical Pictures and Patch Testing In Ad Childrenmentioning
confidence: 99%